1991
DOI: 10.1111/j.1365-2125.1991.tb05600.x
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline stimulates human sperm motility both in vitro and after oral therapy.

Abstract: Pentoxifylline is a haemorrheologic agent often used in the treatment of peripheral vascular disorders. In this study, we measured sperm motility with a trans-membrane migration method and investigated the effect of this drug in the treatment of male infertility. We found that pentoxifylline increased motility of ejaculated spermatozoa in vitro from both normal and asthenozoospermic samples. After giving pentoxifylline to patients with asthenozoospermia for 3 months, sperm motility significantly increased, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
8

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 16 publications
0
28
0
8
Order By: Relevance
“…Hammittet al [9] also reported similar results. Using caffeine, Wolf [25] suggested that decreased linear movement of human sperm is associated with hyperactivation and capacitation, which is supported by the observation of an accelerated rate of capacitation by this chemical [ 191. Pentoxifylline improves sperm motility, but does not significantly increase sperm concentration in infertile men [21]. This agent significantly improved both sperm count and motility in oligoasthenozoospermic patients [ 1 11.…”
Section: Discussionmentioning
confidence: 99%
“…Hammittet al [9] also reported similar results. Using caffeine, Wolf [25] suggested that decreased linear movement of human sperm is associated with hyperactivation and capacitation, which is supported by the observation of an accelerated rate of capacitation by this chemical [ 191. Pentoxifylline improves sperm motility, but does not significantly increase sperm concentration in infertile men [21]. This agent significantly improved both sperm count and motility in oligoasthenozoospermic patients [ 1 11.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sperm treated with pentoxifylline maintain an accelerated movement pattern for several hours [10]. While it is not clear whether this prolonged effect is due to the persistence of phosphodiesterase inhibition resulting in accumulation of cAMP, the reported increased rate of glycolysis due to pentoxifylline could augment intracellular ATP as an energy source and precursor for cAMP.…”
Section: Discussionmentioning
confidence: 64%
“…Experimentally, improved sperm motility can be achieved by increasing intracellular cAMP levels by inhibiting degradation of cAMP by phosphodiesterase with pentoxyfylline [10,14] or caffeine [6]. In other cell systems, the biological effects of VIP are associated with its potency as a stimulator of adenyl cyclase activity leading to increased cAMP synthesis and subsequent activation of protein kineses.…”
Section: Discussionmentioning
confidence: 99%
“…PTX has been considered to stimulate flagellar motility by increasing sperm intracellular cAMP (Stefanovich, 1973;Garbers & Kopf, 1980;Tash & Means, 1983;Ward & Clissold, 1987) as well as by reducing sperm intracellular superoxide anion and reactive oxygen species known to damage DNA (Lopes et al, 1998;Twigg et al, 1998). In particular PTX in both in vivo and in vitro studies, appears to increase significantly beat cross frequency, curvilinear velocity, and the percentage of hyperactivated spermatozoa (Rees et al, 1990;Shen et al, 1991;Lewis et al, 1993;Moohan et al, 1993;Pang et al, 1993;Tournaye et al, 1994;Centola et al, 1995;Paul et al, 1996;Nassar et al, 1999).…”
Section: The Development Of In Vivo Studiesmentioning
confidence: 99%
“…This effect of caffeine on sperm acrosomal cup counteracts the benefits from its role as a motility stimulant . Pentoxifylline (PTX), is the most widely nonselective PDE inhibitor that has been used in assisted reproductive technology programs (Wang et al, 1983;Marrama et al, 1985;Shen et al, 1991;Fuse et al, 1993;Pang et al, 1993;Tournaye et al, 1994). Although its beneficial effect on the outcome of IVF trials in normozoospermic subjects and oligo-asthenozoospermic patients is well documented (Yovich et al, 1988;Yovich et al, 1990;Tasdemir et al, 1993;Yunes et al, 2005) the efficacy of its oral administration to increase sperm fertilizing ability is controversial (Tournaye et al, 1994).…”
Section: The Development Of In Vivo Studiesmentioning
confidence: 99%